Aberrant origin of left vertebral artery: A molecular embryological perspective - Connor Lee McCoy; John Joseph Cichewicz; Rainevan Miller; Soumya Sharma; Adel Maklad; Eistine Boateng (Translational Research in Anatomy)
Background: Variation in the origin and course of the left vertebral artery have surgical and clinical implications in the management of medical conditions. Here, we show variant origin of the left vertebral artery in cadavers and propose potential causes for future molecular investigations. Method: The aortic arches of 32 donors were dissected and observed for anomalous origin of the left vertebral artery in the cadaver laboratory at the University of Toledo, Ohio, USA. Results: Out of 32 donors dissected during laboratory sessions, we observed two cases of the left vertebral artery originating directly from the aortic arch, medial to the left subclavian artery. Conclusion: The study aims to stimulate discussions and future investigations into the molecular embryology of vasculogenesis concomitant with preconceptional and in utero exposures to understand the underlying causes of aberrant origin of the left vertebral artery. Additionally, we speculate that parental and embryonic environmental exposures influence the epigenetic landscape in germ cells and early embryos, thereby contributing to the programming of variant origin of blood vessels.